Profmate: AI-powered lecturer assistant - Loh, Zi Hin (2025)
ProfMate is a cutting-edge AI-powered lecturer assistant aimed at revolutionizing the way academic tasks are managed and executed. The project aims to address the inefficient and timeconsuming aspects of manual grading and administrative duties through the integration of machine learning and automation technologies. ProfMate comprises several core modules: (1) an AI-driven image recognition system designed to assess and validate the accuracy of manually marked papers, identifying missed questions and verifying correct score computation; (2) an automated grade entry tool that streamlines the process of recording and updating student grades; (3) a scheduling interface that facilitates seamless appointment booking between students and lecturers via a shared calendar; (4) a comprehensive login system that distinguishes between student and lecturer access, enabling efficient management of grades, meetings, and review tools; and (5) a results portal that aggregates and presents outcomes from paper reviews and assessments. By leveraging these technologies, ProfMate aims to significantly enhance the efficiency, accuracy, and overall effectiveness of academic administration, thus allowing educators to devote more time to teaching and student engagement. The proposed solution promises to transform educational management, offering a more organised and responsive approach to handling academic tasks.